Progression and Prognosis of Paravalvular Regurgitation After Transcatheter Aortic Valve Implantation - Meneguz-Moreno,Rafael Alexandre (2017)
Abstract Background: The impact of paravalvular regurgitation (PVR) following transcatheter aortic valve implantation (TAVI) remains uncertain. Objective: To evaluate the impact of PVR on mortality and hospital readmission one year after TAVI. Methods: Between January 2009 and June 2015, a total of 251 patients underwent TAVI with three different prostheses at two cardiology centers. Patients were assessed according to PVR severity after the procedure. Results: PVR was classified as absent/trace or mild in 92.0% (n = 242) and moderate/severe in 7.1% (n = 18). The moderate/severe PVR group showed higher levels of aortic calcification (22% vs. 6%, p = 0.03), higher serum creatinine (1.5 ± 0.7 vs. 1.2 ± 0.4 mg/dL, p = 0.014), lower aortic valve area (0.6 ± 0.1 vs. 0.7 ± 0.2 cm2, p = 0.05), and lower left ventricular ejection fraction (49.2 ± 14.8% vs. 58.8 ± 12.1%, p = 0.009). Patients with moderate/severe PVR had more need for post-dilatation (p = 0.025) and use of larger-diameter balloons (p = 0.043). At one year, all-cause mortality was similar in both groups (16.7% vs. 12%, p = 0.08), as well as rehospitalization (11.1% vs. 7.3%, p = 0.915). PVR grade significantly reduced throughout the first year after the procedure (p < 0.01). The presence of moderate/severe PVR was not associated with higher one-year mortality rates (HR: 0.76, 95% CI: 0.27-2.13, p = 0.864), rehospitalization (HR: 1.08, 95% CI: 0.25-4.69, p=0.915), or composite outcome (HR: 0.77, 95% CI: 0.28-2.13, p = 0.613). Conclusion: In this sample, moderate/severe PVR was not a predictor of long-term mortality or rehospitalization. (Arq Bras Cardiol. 2017; [online].ahead print, PP.0-0)